Prevalence of Musculoskeletal Disorders and Associated Risk Factors among Selected Factory Workers in Penang, Malaysia - Lim, Mei Qi; Vinodhkumar, Ramalingam (INTI International University, 2019)
Background: Musculoskeletal Disorders (MSDs) described as the major work-related health issue among the industrial workers by exposing to physical factors like overuse, poor posture and heavy lifting in the work setting. Objective: To determine the prevalence of MSDs and associated risk factors among factory workers of a selected company in Penang, Malaysia. Methodology: A detailed validated questionnaire contributed to MSDs were administrated to 626 workers in the company. The participants were 403 female and 223 male workers volunteers to participate in this study. Data analyzed with the use of SPSS Window Version 21.0, Pearson 2 used to identify the relationship between musculoskeletal pain and the participants risk factors. Results: The result showed that the highest prevalence rate was 45.4% of cases musculoskeletal disorders by the factory workers. The most common MSDs among the workers are shoulder (21.8%) followed by lower back (18.7%), upper back (14%) and neck region (13.6%). Among all the workers, Chinese ethnicity workers those who work in the 12-hour shift (71.4%) likely to get MSDs compared to workers in 8 hours shift (28.6%). The Chi-square statistics showed a significant association between the working hours and the pain symptoms (2 (1), N = 17) = 4.496, p < .05). Whereas the participant's age, gender, work performance, and sleep patterns were not associated with the MSDs in this study. Conclusion: This study concluded the prevalence rate is moderately high and recommends establishing MSDs intervention at workplaces and awareness training as an integral part to reduce the risk factors.